Major, trace and rare earth elemental geochemistry of Santonian–Campanian onland‐offshore transition in a Gilbert‐type deltaic setting, Cauvery Basin, southern India. Issue 10 (13th June 2022) - Ramkumar, Muthuvairavasamy; Fathima, AL; Nagarajan, Ramasamy; Santosh, M.; Menier, David
Abstract : The spatially widely distributed and temporally protracted Santonian–Campanian stratigraphic records of the Sillakkudi Formation of the Ariyalur Group, Cauvery Basin, southern India represent an onland exposure of a Gilbert‐type delta. Here, we present geochemical, mineralogical, and petrographic analyses of two composite stratigraphic sections, and evaluate the climatic, tectonic, and other factors that contributed to the spatio‐emporal uniqueness of this formation. A range of low to intensive weathering, simultaneous exhumation/erosion, physical transport, and chemical weathering, prevalent at different parts of the source region and or the existence of multiple channels that drained varied source regions and hence varied lithologies at exhumation surfaces which in turn experienced seasonally varied flow conditions were interpreted. The prevalence of physical erosion during the initial stages of the deposition of the Sillakkudi Formation that progressed towards higher intensities of chemical weathering, in tune with the increase in atmospheric temperature and sea‐level rise during the later stages of the formation, is evidenced. Occurrences of positive and negative Eu anomalies and a progression from active to passive tectonic setting of samples, concomitant with change from tectonic control to relative sea‐level and the sediment influx controlled nature of deposition from Santonian–Campanian is recorded. Together, three sets of related factors namely, tectonics, increase of atmospheric temperature and sea‐level rise operated independently, and the enforced transience of transformation of the source terrain from active to passive margin, the transformation of depositional setting from fluvial to estuarine/intertidal to open marine, and shifting of principal loci of deposition from onland to offshore, are documented. The causal link between the progressive increase of sea‐level control over the depositional system during the Santonian–Campanian as recorded by this study could be due to the rise in atmospheric temperature that in turn might have been influenced by the movement of the Indian Plate from low latitudes towards the equatorial region. The second implication of the results is that the studies attempting to document tectonic setting, provenance, and weathering, with the help of geochemical discriminant diagrams, should also consider the spatial and temporal changes in the source area as well as depositional setting. Abstract : The manuscript deals with the documentation of palaeotectonics, provenance, weathering climate, and depositional environment prevalent during Santonian–Campanian in a unique Gilbert‐type delta in the Cauvery Basin, southern India and attempts to interpret them in terms of lithological‐climatic‐tectonic control during the transience of onland‐offshore depositional regime of the delta and has implications on the application of the same elsewhere in similar settings.